Beyond Mitigation : Potential Options for Counter-Balancing the Climatic and Environmental Consequences of the Rising Concentrations of Greenhouse Gases - MacCracken, Mike (2012)
Global climate change is occurring at an accelerating pace, and the global greenhouse gas (GHG) emissions that are forcing climate change continue to increase. Given the present pace of international actions, it seems unlikely that atmospheric composition can be stabilized at a level that will avoid "dangerous anthropogenic interference" with the climate system, as called for in the UN Framework Convention on Climate Change. Complicating the situation, as GHG emissions are reduced, reductions in the offsetting cooling influence of sulfate aerosols will create an additional warming influence, making an early transition to climate stabilization difficult. With significant reductions in emissions (mitigation) likely to take decades, and with the impacts of projected climate change-even with proactive adaptation-likely to be quite severe over the coming decades, additional actions to offset global warming and other impacts have been proposed as important complementary measures. Although a number of possible geoengineering approaches have been proposed, each has costs and side effects that must be balanced against the expected benefits of reduced climate impacts. However, substantial new research is needed before comparison of the relative benefits and risks of intervening is possible. A first step in determining whether geoengineering is likely to be a useful option is the initiation of research on four interventions to limit the increasing serious impacts: limiting ocean acidification by increasing the removal of carbon dioxide from the atmosphere and upper ocean; limiting the increasing intensity of tropical cyclones; limiting the warming of the Arctic and associated sea level rise; and sustaining or enhancing the existing sulfate cooling influence. In addition, in depth consideration is needed regarding the governance structure for an international geoengineering decision-making framework in the event that geoengineering becomes essential.